(untitled) (Publicaciones en Ciencias y Tecnología, 2025)
This paper shows the technical considerations to be taken into account for the conceptual design of an allyl chloride production reactor based on the methodology proposed by Krishna and Sie (1994), which consists of three levels: a) catalyst design, b) dispersion strategy of the reactant and energy and c) selection of the hydrodynamic flow regime. When selecting the configuration of a reactor, it is desired that it complies with a "Wish List", which refers to all the needs or requirements, such as maximum conversion and selectivity, easy operation, lower capital and operating costs, which are needed to achieve the best possible design of the equipment. Following the guidelines of the methodology, to begin with, the design of the catalyst was proposed, in this sense an extruded cylindrical morphology of CuCl2 eggshell type was selected. Once the catalyst design was established and, based on this, the injection of the feed to the system in stages was considered, with the purpose of maintaining a controlled chlorine concentration throughout the reactor, thus avoiding the formation of 2-3 dichloropropene, which is an undesired product. As a final instance, the hydrodynamic flow regime of the reactive system for the production of allyl chloride via direct chlorination of propylene was determined, the decision was based on taking into account strategies I and II, where a fixed bed configuration with an axial flow arrangement was the most suitable for the catalytic process. Likewise, it was considered to work in a non-adiabatic operating condition in a multitubular reactor (tube and shell), since there will be a heat transfer with the external medium (coolant).